CdSe/ZnS quantum dots induce hepatocyte pyroptosis and liver inflammation via NLRP3 inflammasome activation. (June 2016) - Lu, Yonghui; Xu, Shangcheng; Chen, Haiyan; He, Mindi; Deng, Youcai; Cao, Zhengwang; Pi, Huifeng; Chen, Chunhai; Li, Min; Ma, Qinlong; Gao, Peng; Ji, Yan; et al.
Abstract: Increased biomedical applications of quantum dots (QDs) have raised considerable concern regarding their toxicological impact. However, the toxicity of QDs is largely unknown and the underlying mechanism is still undefined. This study was conducted to examine the hepatotoxicity of CdSe/ZnS core/shell QDs and the underlying mechanism. In hepatic L02 cells, the QDs caused cytotoxicity in a dose-dependent manner. The QDs were then shown to activate the NLR pyrin domain containing 3 (NLRP3) inflammasome in hepatocytes, leading to a novel pro-inflammatory form of cell death named pyroptosis. Further experiments demonstrated that the QDs induced mitochondrial reactive oxygen species (mtROS) production, and that both a mtROS and a total ROS scavenger attenuated QDs-induced NLRP3 activation and pyroptosis. In addition, QDs increased cytoplasmic calcium (Ca 2+ ) levels, while a Ca 2+ release antagonist and chelator alleviated QDs-induced mtROS, NLRP3 activation and subsequent pyroptosis in hepatocytes. In vivo, QDs administration induced liver inflammation and dysfunction. Moreover, the QDs also resulted in NLRP3 activation in liver tissue. However, QDs-induced liver inflammation and dysfunction were abolished in NLRP3 knockout mice. Also, an elevation in mtROS was observed in liver after QDs administration, and the mtROS scavenger suppressed liver NLRP3 activation, inflammation and dysfunction induced by QDs. Our data suggest that QDs induced hepatocyte pyroptosis, liver inflammation and dysfunction via NLRP3 activation, which was caused by QDs-triggered mtROS production and Ca 2+ mobilization. Our results provide novel insights into QDs-induced hepatotoxicity and the underlying mechanism, facilitating control of the side effects of QDs.